Effectiveness, economics, and safety of drop nets and helicopters with net‐gunning for capturing white‐tailed deer. (27th September 2022) - Beaver, Jared T.; Grantham, Chad; Lucas Cooksey, M.; Skow, Kevin; Pierce, Brian L.; Lopez, Roel R.
Abstract: Capture and handling of animals is an essential component of wildlife research. Human population growth, coupled with rapid land use changes, have resulted in increased wildlife‐human interactions and subsequently increased public awareness and sensitivity to animal welfare. However, few publications have compared capture techniques in terms of effectiveness, economics, and animal safety across the same environment. We evaluated capture effectiveness, monetary cost, and safety for drop nets and both single and tandem helicopters with net‐gunning techniques for white‐tailed deer ( Odocoileus virginianus ; deer). We captured 32 (drop nets), 68 (single helicopter), and 71 (tandem helicopters) deer over 6 study periods (3 autumn and 3 spring) from August 2011 to February 2014. Catch‐per‐unit‐effort (CPUE, person hours/deer) was lowest for tandem helicopters (2.3) followed by single helicopter (2.7) and then drop nets (65.8). Animals captured using drop nets heavily favored younger males compared to both helicopter and net‐gunning techniques. Capture cost (total cost/deer) was greater for drop nets ($655 USD) than either single helicopter ($164) or tandem helicopters ($231). Total mortality (capture‐related and postcapture myopathy) was highest for drop nets at 12.5% followed by 5.9% for single helicopter and 4.2% for tandem helicopters. While all 3 techniques were safe and effective methods for deer capture, the tandem helicopter technique was superior in balancing effectiveness, cost, safety, and maximizing spatial coverage, all of which must be considered when selecting among available capture methods. Abstract : We evaluated capture effectiveness, monetary cost, and safety for drop net and both single and tandem helicopter with net‐gun techniques for white‐tailed deer. While all three techniques were safe and effective methods for deer capture, the tandem‐helicopter technique was superior in balancing effectiveness, cost, safety, and maximizing spatial coverage, all of which must be considered when selecting among available capture methods.